Impact of age on acute post-TBI neuropathology in mice expressing humanized tau: a Chronic Effects of Neurotrauma Consortium Study. (24th August 2018) - Mouzon, Benoit; Saltiel, Nicole; Ferguson, Scott; Ojo, Joseph; Lungmus, Carlyn; Lynch, Cillian; Algamal, Moustafa; Morin, Alexander; Carper, Benjamin; Bieler, Gayle; Mufson, Elliott J.; Stewart, William; et al.
ABSTRACT: Objectives : We hypothesized that polypathology is more severe in older than younger mice during the acute phase following repetitive mild traumatic brain injury (r-mTBI). Methods : Young and aged male and female mice transgenic for human tau (hTau) were exposed to r-mTBI or a sham procedure. Twenty-four hours post-last injury, mouse brain tissue was immunostained for alterations in astrogliosis, microgliosis, tau pathology, and axonal injury. Results : Quantitative analysis revealed a greater percent distribution of glial fibrillary acid protein and Iba-1 reactivity in the brains of all mice exposed to r-mTBI compared to sham controls. With respect to axonal injury, the number of amyloid precursor protein-positive profiles was increased in young vs aged mice post r-mTBI. An increase in tau immunoreactivity was found in young and aged injured male hTau mice. Conclusions : We report the first evidence in our model that r-mTBI precipitates a complex sequelae of events in aged vs young hTau mice at an acute time point, typified by an increase in phosphorylated tau and astroglisosis, and a diminished microgliosis response and axonal injury in aged mice. These findings suggest differential age-dependent effects in TBI pathobiology.